Driving Aviation Performance with Knowledge Management Metrics and Key Performance Indicators: A Quantitative Analysis - El Asri, Hayat; Tsiakalos, Serafeim; Anakkar, Kacim Thami (Journal of Knowledge Management Practice, 2025)
This study examines the impact of Knowledge Management (KM) metrics and Key Performance Indicators (KPIs) on operational effectiveness in the aviation industry, focusing on regulatory compliance and technological integration. A six-month survey across eleven countries assesses how organizational characteristics, individual factors, and technology adoption influence KM practices. Findings reveal that regulatory frameworks and industry standards shape KM strategies, while organizational size and individual experience have minimal impact. A strong link between technology adoption and KM underscores the role of advanced tools like knowledge-sharing platforms in enhancing operational resilience. The study advocates for technology-driven KM strategies aligned with industry standards to improve safety, efficiency, and innovation. By refining KM metrics and integrating technology, aviation organizations can enhance knowledge-sharing and performance. This research fills a gap in KM literature by addressing sector-specific challenges and providing actionable strategies for aligning KM with technological advancements and regulatory requirements, offering a roadmap for operational resilience in this highly regulated industry.